Social Media Impact on Covid-19 Vaccination among Students with Positive Perceptions in Health Department of Politeknik Negeri Madura - Syakura, Abdan; Amin, Edy Suryadi; Denta, Anggeria Oktavisa (Alta Dharma Publisher, 2022)
Background: One of the critical information systems conveyed through social media is health education. Objective: This study aims to determine social media's impact on covid-19 vaccination among students with the positive Health department of Politeknik Negeri Madura. Method: This study uses a descriptive design, The population in this study was 194 students from all semesters of the 2021-2022 academic year. The sample in this study was the entire population taken using a total sampling technique. The variables of this study were information sources for students who have positive perceptions about the covid-19 vaccination. The instrument used is a questionnaire containing data about the use of information sources for students who have positive perceptions about vaccines. Assessment of student perceptions using a Likert scale questionnaire. A Likert scale calculation using a T score to analyze the data used to determine student perceptions. The test results are then compared with T tables, and conclusions are drawn. Results: Table 2 shows that most respondents (68%) have the largest source of information about covid-19 through social media communication and none of the respondents (0%) get information from village officials. Recommendation: the role of academics is critical in increasing students' knowledge about literacy sources and reading research results in scientific articles